2010
DOI: 10.1021/jp101447r
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of α-Helical Structure and Cyanylated Cysteine on Each Other

Abstract: β-Thiocyanatoalanine, or cyanylated cysteine, is an artificial amino acid that can be introduced at solvent-exposed cysteine residues in proteins via chemical modification. Its facile post-translational synthesis means that it may find broad use in large protein systems as a probe of site-specific structure and dynamics. The C≡N stretching vibration of this artificial side chain provides an isolated infrared chromophore. To test both the perturbative effect of this side chain on local secondary structure and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 62 publications
3
46
0
Order By: Relevance
“…Correspondingly, the use of either CN or N 3 probes to study the folding of nSH3 would have erroneously suggested a multistep folding process involving the population of intermediates, as opposed to the simple two-state process revealed by the use of the non-perturbative CÀD probes (Figure 3). The results of this systematic analysis using nSH3 adds to a growing literature [3,13,19,24,35] that suggests that these probes are destabilizing, and combined these results suggest that the destabilization may be general. Thus, in contrast to CÀD labels, which are strictly non-perturbative, the results of studies based on the use of CN and N 3 probes must be interpreted with caution to ensure that they are biologically relevant and not an artifact of the chromophore or its perturbation of the protein.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Correspondingly, the use of either CN or N 3 probes to study the folding of nSH3 would have erroneously suggested a multistep folding process involving the population of intermediates, as opposed to the simple two-state process revealed by the use of the non-perturbative CÀD probes (Figure 3). The results of this systematic analysis using nSH3 adds to a growing literature [3,13,19,24,35] that suggests that these probes are destabilizing, and combined these results suggest that the destabilization may be general. Thus, in contrast to CÀD labels, which are strictly non-perturbative, the results of studies based on the use of CN and N 3 probes must be interpreted with caution to ensure that they are biologically relevant and not an artifact of the chromophore or its perturbation of the protein.…”
supporting
confidence: 56%
“…Since the H bonds involved are introduced by the probe itself, this renders the data difficult to interpret in terms of the native protein. Boxer and co-workers have noted that it is possible to quantify the contribution of local electrostatics to nitrile peak shifts based on the relationship of IR frequency shifts and 13 C NMR chemical shifts, [5,14] and our data suggest that such corrections are likely to be necessary. Moreover, the data reveal that both extrinsic probes are prone to perturb the protein.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…A lack of complete quantitative agreement between all DPC-bound CD spectra indicates that there is a small perturbative influence of each C* placement on CM15’s DPC-bound structure; this is not particularly surprising in the context of recent measurements of C*’s effect on the helical stability of alanine-repeat peptides. (27) Whether these secondary structural changes affect the orientation of the peptide with respect to the micelle cannot be determined from CD spectra, which report only on the relationships between backbone amide groups of the peptide.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, cyanylated cysteine, in which the cysteine thiol has been converted into a thiocyanate, has been the subject of several studies. [37][38][39][40] These studies illustrate that the thiocyanate is very sensitive to its local environment, making it an excellent probe of the local dynamics. Furthermore, because it is prepared by modifying cysteine in the protein, the synthetic methods to incorporate the probe site selectively are straightforward.…”
Section: Introductionmentioning
confidence: 86%